Mammalian SLC39A13 promotes ER/Golgi iron transport and iron homeostasis in multiple compartments - Huihui Li; Yanmei Cui; Yule Hu; Mengran Zhao; Kuanyu Li; Xiaoyun Pang; Fei Sun; Bing Zhou (Nature Communications)
Abstract Iron is a potent biochemical, and accurate homeostatic control is orchestrated by a network of interacting players at multiple levels. Although our understanding of organismal iron homeostasis has advanced, intracellular iron homeostasis is poorly understood, including coordination between organelles and iron export into the ER/Golgi. Here, we show that SLC39A13 (ZIP13), previously identified as a zinc transporter, promotes intracellular iron transport and reduces intracellular iron levels. ZIP13 loss causes an iron deficiency in the ER/Golgi and other intracellular compartments, such as lysosomes and mitochondria, as well as elevating iron in the cytosol. ZIP13 overexpression has the opposite effect, increasing iron in organellar compartments. We suggest that ZIP13 gatekeeps an iron trafficking route that shunts iron from the cytosol to the ER/Golgi hub. Zip13-knockout male mice have iron deposition in several tissues. These data demonstrate that mammalian ZIP13 is crucial for iron homeostasis and suggest a potential iron transport function.